Seminar Dan Pelatihan Peningkatan Pembukuan Dan Upaya Pencegahan Fraud Berbasis Digital Bagi Pelaku UMKM di Lembang Ullin - Mince Batara; Zerah Rut Binti Ruben; Virginia Parorrongan; Lisa Bunga; Jesika Tampa Padanun (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Community service is a tangible manifestation of a spirit of caring for others. In the context of special needs education, the State Special School in Banjarbaru City faces several challenges, especially in the assessment process of special needs children. Limitations in human resources in terms of teaching staff and technology, as well as conventional assessment methods, are the main obstacles. The solution came in the form of the Special Needs Children Assessment Application called APBAKUS in 2018. Community service through training and socialization of APBAKUS usage in 2019 encouraged the application's utilization. The results of the community service were highly positive, evident in increased efficiency in assessment timing, more coordinated data management, and the improved capabilities of teachers in overcoming obstacles. The APBAKUS application played a crucial role in enhancing the quality of educational services at the State Special School in Banjarbaru City, enabling teachers to provide better services tailored to the needs of special needs children. Thus, community service reflects the spirit of assisting and improving the quality of education for children who require special attention within the community.